Preparation And Characterization Of Natural Rubberchitson Biodegradable Urea For Slow Release Fertilizer - Abdul Hamid, Nor Nadiah (UTeM, 2016)
Chitosan and natural rubber are highly potential materials to be blended together in urea fertilizer for slow release properties due to its gel forming ability and hydrophobicity, respectively. This study investigates the potential of chitosan and natural rubber incorporation to replace formaldehyde in urea fertilizers. On the first stage, the effect of chitosan content and gelatinization temperature on physical properties of chitosan based urea fertilizer were studied. The chitosan content was varied from 0, 3, 5, 7 and 10 pph at two different mixing temperatures (gelatinization temperature) which are 60oC and room temperature of 25 ± 3oC. Chitosan based urea fertilizer was prepared through a direct wet mixing using laboratory set up consist of beaker, magnetic stirrer and hotplate. Subsequently, the mixture was then dried in an oven at 60oC for 8 hours and compacted into pellets form for further testing and analyses. For the first stage, gelatinization process at room temperature was observed to produce samples which exhibited better water absorption and water retention capability than the one gelatinized at 60oC. The results were supported by XRD analyses. In this study, the formulations which showed good balance between water absorption and water retention was chitosan based urea fertilizer filled with 3 to 7 pph chitosan content. Both gelatinization temperatures produced fertilizer with significant crystallinity in its structure. In overall, gelatinization process at room temperature indicates better performance as well as cost effective. The next stage was performed to investigate the potential of natural rubber (NR) as hydrophobicity contributor to the chitosan based urea fertilizer. In this stage, constant chitosan content at 5 pph was used to be incorporated with NR for preparation of binder. The NR content was varied from 0, 3, 5, 7 and 10 pph. In this stage, chitosan and NR were diluted in toluene with the presence of bentonite as filler. Testing for water absorption, water retention, soil burial degradation, hardness and compression test were carried out. The findings were supported by Fourier Transform Infrared analysis, Diffrential Scanning Calorimetry (DSC) analysis, X-ray Diffraction (XRD) as well as Scanning Electron Microscopy (SEM). Based on ranking method, it was proven that, chitosan based urea fertilizers with the highest content of natural rubber (10phr) shows the highest rank desired for the characteristics needed. Fertilizer with 5 pph chitosan and 10 pph NR exhibited the highest water absorption capability, the highest water retention ability, appreciable compression strength and hardness as well as the slowest rate in soil burial degradation. Uniform distribution of NRchitosan rich domains in the fertilizers depicted improvement in encapsulation of urea particles for fertilizers with 10 pph NR loading if compared to the fertilizer without NR. This study had proven the potential of chitosan and natural rubber in replacing formaldehyde for agriculture urea fertilizers.